1990
DOI: 10.1016/0248-4900(88)90012-3
|View full text |Cite
|
Sign up to set email alerts
|

Polarizing microscope study of a contractile nanofilament system: the Acantharian myoneme

Abstract: The distribution of post-translationally modified forms of tubulin has been studied in mouse oocytes arrested in meiotic metaphase II and in interphase eggs after fertilisation. Tyrosinated and acetylated microtubules are present in the meiotic spindle but detyrosinated ones are not. Acetylation only occurs in the most stable subpopulation of microtubules in the spindles ("pole to kinetochore"). After fertilisation, many microtubules of the interphase array become acetylated, but detyrosination occurs only at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…He concluded that the undulation is generated by the axoneme using ATP hydrolysis and that the retraction can be induced by Ca 2+ without any requirement for ATP. The mechanism of contraction could be explained, as shown by polarizing microscopy by Febvre et al [23] in the case of the myonemes of Acantharia, through the pitch variations of the filaments coiling.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…He concluded that the undulation is generated by the axoneme using ATP hydrolysis and that the retraction can be induced by Ca 2+ without any requirement for ATP. The mechanism of contraction could be explained, as shown by polarizing microscopy by Febvre et al [23] in the case of the myonemes of Acantharia, through the pitch variations of the filaments coiling.…”
Section: Discussionmentioning
confidence: 96%
“…Other organelles such as the myonemes of Acantharia [19][20][21][22][23] appear similar both in their structure and behaviour. They are able to shorten to 3 0 -4 0 % of their length within 10-15 ms.…”
Section: Discussionmentioning
confidence: 99%
“…ac-α-tubulin is present in various microtubule structures, including primary cilia, centrioles, and the mitotic spindle, and may have a role in stabilizing these structures [ 30 ]. In addition, ac-tubulin has been found in oocytes [ 31 , 32 ]. Our data showed that specific KD of Kif4a reduced acetylation of tubulin in oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Even, SIRT2 has been found on the spindle, however, in contrast to our observation, SIRT2 occupies uniquely metaphase I spindle [48]. Surprisingly, the deacetylating action of HDACs on the spindle tubulin is considered a phenomenon essential for metaphase II spindle assembly in oocytes [44, 46], although tubulin acetylation is a marker of stable microtubules [49]. On the other hand, SIRT1 may contribute to microtubule polymerisation via alternative PLK1 regulation [50] through equal localisation on the oocyte spindle.…”
Section: Discussionmentioning
confidence: 64%